2018
DOI: 10.2147/tcrm.s159211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ramosetron and ondansetron for the treatment of established postoperative nausea and vomiting after laparoscopic surgery: a prospective, randomized, double-blinded multicenter trial

Abstract: BackgroundPostoperative nausea and vomiting (PONV) is a common complication after surgery, which increases physical and psychological discomfort and delays recovery. The aim of this study was to test the hypothesis that ramosetron is comparable to ondansetron for the treatment of established PONV after laparoscopic surgery using a prospective, randomized, double-blinded, noninferiority study.MethodsPatients who had at least two risk factors of PONV and underwent laparoscopic surgery under general anesthesia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In patients with established PONV (with or without prior PONV prophylaxis), common rescue treatment includes ondansetron, promethazine, and droperidol. [89][90][91] Several additional rescue treatments have been proposed, as summarized below.…”
Section: Novel Rescue Treatmentmentioning
confidence: 99%
“…In patients with established PONV (with or without prior PONV prophylaxis), common rescue treatment includes ondansetron, promethazine, and droperidol. [89][90][91] Several additional rescue treatments have been proposed, as summarized below.…”
Section: Novel Rescue Treatmentmentioning
confidence: 99%
“…Of the 17 remaining studies considered eligible for the detailed evaluation, 11 articles were excluded as irrelevant after reviewing the full manuscript. Finally, the data from six studies [19][20][21][23][24][25] involving 361 patients in the ondansetron group and 326 patients in the ramosetron group were included in the meta-analysis. A detailed flow diagram of the study selection process is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3, five studies 19,20,[23][24][25] in 614 patients examined the incidence of POV (ondansetron, n ¼ 326; ramosetron, n ¼ 288). A meta-analysis of the results of these studies showed that there was no statistically significant difference in the incidence of POV between the two treatment groups at different time intervals within the 24-hour period after laparoscopic surgery.…”
Section: Povmentioning
confidence: 99%
See 2 more Smart Citations